2000
DOI: 10.1023/a:1008967104082
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although the subjective nature of quality of life is generally accepted, less attention has been paid to the procedure of selecting domains to be explored with questionnaires. To explore what contributes to cancer patients' quality of life, a survey was conducted with the aim of identifying contents of quality of life using cancer patients as 'experts'. A questionnaire with open-ended items aimed at exploring the meaning of quality of life and at determining the contents of health and not health related qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Half of the included studies were conducted among patients with cancer [15, 16, 18, 19, 21, 22, 24, 28, 34, 35, 41, 44, 47, 5052, 55, 56], whereas the other studies included patients with a range of other somatic illnesses (see Table 3). In three studies, the patient sample consisted of a combination of both patients with cancer and patients with another somatic illness [38, 39, 45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of the included studies were conducted among patients with cancer [15, 16, 18, 19, 21, 22, 24, 28, 34, 35, 41, 44, 47, 5052, 55, 56], whereas the other studies included patients with a range of other somatic illnesses (see Table 3). In three studies, the patient sample consisted of a combination of both patients with cancer and patients with another somatic illness [38, 39, 45].…”
Section: Resultsmentioning
confidence: 99%
“…In the remaining studies, QoL domains were identified by means of a telephone interview [53], focus groups [47], or a questionnaire employing open-ended questions [43, 46, 52]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the patients’ perspective is the gold standard for the measurement of health related quality of life and as a result, they should be the primary source regarding what issues are to be included in a health related quality of life (HRQOL) assessment tool [ 4 ]. Patients are best able to define and measure their own HRQOL because it is such a subjective experience [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to content in QOL assessment tools, it is generally accepted that the patient perspective is the gold standard [ 22 ]. Since patient experiences can be subjective, one’s definition and measure of issues can differ starkly from another.…”
Section: Discussionmentioning
confidence: 99%